How can we optimise antifungal use in a solid organ transplant centre? Local epidemiology and antifungal stewardship implementation: A single‐centre study. Issue 7 (18th May 2020) - Mularoni, Alessandra; Adamoli, Lucia; Polidori, Piera; Ragonese, Barbara; Gioè, Santi Mauro; Pietrosi, Astrid; Tuzzolino, Fabio; Guadagnino, Giuliana; Monaco, Francesco; Grossi, Paolo Antonio; Conaldi, Pier Giulio; Luca, Angelo; et al.
Abstract: Purpose: We aimed to implement and to assess the impact of the antifungal stewardship programme (AFSp) on prescription appropriateness of antifungals, management and outcomes of candidaemia patients, and antifungal consumption and costs at our solid organ transplant (SOT) institute. Methods: Local epidemiology of invasive fungal infections (IFIs) from 2009 to 2017 was analysed in order to prepare an effective AFSp, implemented in January 2018. It included suspension of empirical antifungal prescriptions after 72 hours (antifungal time‐out), automated alert and infectious disease (ID) consult for empirical prescriptions and for every patient with IFI, and indication for step‐down to oral fluconazole when possible. We used process measures and results measures to assess the effects of the implemented programme. Results: The ASFp led to significant improvements in selection of the appropriate antifungal (40.5% in pre‐AFS vs 78.6% in post‐AFS), correct dosing (51.2% vs 79.8%), correct length of treatment (55.9% vs 75%) and better management of patients with candidaemia. Analysis of prescribed empirical antifungal revealed that defined daily doses (DDDs) per 100 patient days decreased by 36.7% in 2018 compared to the average of pre‐AFSp period, with important savings in costs. Conclusion: This AFSp led to a better use of antifungal drugs in terms of appropriateness and consumption, with stable clinical and microbiological outcomes in patients with IFI.